Target versus ball focused aiming when putting: What has been done and what has been missed - Moffat, D.; Collins, D.; Carson, H. J. (International Journal of Golf Science, 2017)
As the prevalence of target focused aiming in golf putting increases among professionals and amateurs alike, it is important to understand its operation if the synergy between research and practice is to be optimized. Therefore, the current paper's aims were firstly to review and critique existing empirical literature. Although our observations of these studies were informative, however, we identified a number of key methodological inconsistencies and omissions, which limits our understanding as a complete evidence-base across studies. Consequently and secondly, we provide insight into possible mechanisms for how target focused aiming might work with corresponding measures for investigating these suggestions. Finally, we propose a number of methodological considerations that need to be addressed by future research. It is hoped this research will inform future practice when coaching the skill of putting. ABSTRACT FROM AUTHOR